Secukinumab use in the treatment of Netherton's syndrome. (27th May 2022) - Gan, Christian; King, Emma; Orchard, David
Abstract: Netherton syndrome is a rare, severe genetic disorder of cornification without specific treatment. We describe two cases who demonstrated marked cutaneous improvement with secukinumab and suggest a role for IL‐17 therapy in treating this condition.